The Theory of Functions of a Real Variable (Second Edition) - Jeffery, R. L. (Book collections on Project MUSE., 1951)
This textbook leads the reader by easy stages through the essential parts of the theory of sets and theory of measure to the properties of the Lebesgue integral.